Synthesis of nitropyrimidines as inactivators of 0-6-Methylguanine-DNA Methyltransferase - Fernandez, Sergio Lopez (Trinity College (Dublin, Ireland). School of Chemistry, 2009)
The cytotoxic effects of the chemotherapeutic N-(2-chloroethyl)-N-nitrosoureas (e.g. BCNU, CCNU, fotemustine) and the related methylating agents (e.g. DTIC, procarbazine, temozolomide) are primarily a consequence of their ability to alkylate DNA at the O -6 position of guanine. This lesion can ultimately cause the death of the targeted cancer cell. However, it is well established that resistance to these O -6 alkylating agents can be mediated by the DNA repair protein O6-methylguanine-DNA methyltransferase (MGMT). This repair protein MGMT is the primary source of resistance that many tumours exhibit to chemotherapeutic agents which modify the O -6 position of DNA guanine residues. Inactivation of this protein by treatment with pseudosubstrates prior to the administration of alkylating agents enhances the cytotoxic effects of these chemotherapeutic agents.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin.